Semantics in the factual interpretation of the approximate truth concept of the bioecotoximonitor. - Argota-Pérez, George (2024)
The aim of the study was to analyze the semantics in the factual interpretation of the concept of approximate truth of the bioecotoximonitor. The transformation of the biomonitor to the quality of bioecotoximonitor was considered for analysis, along with the monist, pluralist, and instrumentalist distinction during bioassessment with the bioecotoximonitor. Five criteria were indicated: environmental conditions, data interpretation, interpretation consistency, environmental variability impact, and applicability in bioassessment. The factual interpretation of the bioecotoximonitor, through five criteria, evaluates the understanding of truth in environmental systems. It emphasizes the importance of considering environmental conditions and flexible data interpretation. The structured criteria address from collection to practical application in environmental management, ensuring the relevance and applicability of the information collected in specific environmental contexts. It is concluded that semantic criteria structure the factual interpretation of approximate truth where considering environmental conditions ensures result relevance, and interpretation from multiple perspectives is crucial for precise understanding.